Identifying measurement knowledge and its relationship to engineering design. (9th October 2014) - Saunders, P.; Giudice, S.; Swart, J.
Abstract : Capable measurement of the size and shape of components is a prerequisite for precision manufacturers. However, the design community may not fully consider measurement issues that could arise when components are manufactured, and the manufacturing community may not wholly appreciate the value that measurement data can bring to design. This paper investigates measurement knowledge in this relationship to find out if there are specific knowledge types that could be developed to improve the likelihood of fulfilling design intent. A proven systems-based approach was applied to an illustrative case to develop a model of knowledge flows and identify key knowledge types. For this case study, it was found that knowledge about measurement is dispersed and managed through a variety of practices which are relatively isolated from design. Furthermore, conflict was uncovered between the knowledge types, reinforcing the view that a more inclusive and integrated approach is required. In the course of the research, a novel methodology was developed in which group modelling was used to generate questions, rather than the more typical approach of grounding a systems model on interview data.